Integrasi Model Bisnis Franchise MXBC dan Peluang Ekspansi ke Kawasan Asia Timur Tengah - Suprapto, Yandi; Maitri, Badra; Jesslyn, Jesslyn; Larissa, Jesslyn; Liana, Jumi (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this study is to identify the franchise business model used by Mixue Ice Cream & Tea company. This corporate case study also aims to highlight the significance of licenses in managing a global supply chain business. The study methodology used is a qualitative approach with supporting information from news, scientific publications, and other sources. According to the findings of the case study of the Mixue Ice Cream & Tea Company, it was made possible by the necessity of halal licensing and other variables that allowed for business expansion potential in the Middle East and Asia. Keywords: Franchise, Licence, Intellectual Property Rights, Expansion, Middle East Asia